Measurements of sensor radiation damage in the ATLAS inner detector using leakage currents - Aad, G.; Abbott, B.; Abbott, D. C.; Abud, A. Abed; Abeling, K.; Abhayasinghe, D. K.; Çetin, Serkant Ali (Iop Publishing Ltd, 2021)
Non-ionizing energy loss causes bulk damage to the silicon sensors of the ATLAS pixel and strip detectors. This damage has important implications for data-taking operations, charged-particle track reconstruction, detector simulations, and physics analysis. This paper presents simulations and measurements of the leakage current in the ATLAS pixel detector and semiconductor tracker as a function of location in the detector and time, using data collected in Run 1 (2010-2012) and Run 2 (2015-2018) of the Large Hadron Collider. The extracted fluence shows a much stronger vertical bar z vertical bar-dependence in the innermost layers than is seen in simulation. Furthermore, the overall fluence on the second innermost layer is significantly higher than in simulation, with better agreement in layers at higher radii. These measurements are important for validating the simulation models and can be used in part to justify safety factors for future detector designs and interventions.
Keywords: Radiation Damage To Detector Materials (Solid State); Detector Modelling And Simulations I (İnteraction Of Radiation With Matter, İnteraction Of Photons With Matter, İnteraction Of Hadrons With Matter, Etc); High-Energy; Displacement Damage; Residual Nuclei; Hadron-Nucleus